Relationship among E-Learning Systems, Self-Regulation, and Loneliness in a Blended Learning Context - Thomas, Darrin (ASEAN Journal of Education, 2023)
The growing popularity of e-learning has led to unforeseen consequences. With the rise of e-learning has also come a rise in loneliness among students who are isolated socially. However, there is little data in the context of blended learning with e-learning attitudes and loneliness. Therefore, the purpose of this study was to examine the relationships of loneliness and e-learning self-regulation with e-learning systems in a blended learning context. Using structural equation modeling, a sample was drawn from 148 university students based in Thailand. The results indicated that loneliness has no relationship with e-learning self-regulation and no direct or indirect relationship with e-learning systems. The final model explained 41% of the variance of e-learning systems. This indicates that loneliness may not be a significant factor when schools switch to blended learning rather than fully online teaching.